Is it all too bad to return to Marx? marxism and reformism at the central compilation and translation bureau from Hu Jintao to Xi Jinping - Chow Bing, N. (2013)
The Central Compilation and Translation Bureau (CCTB), a central organ of the Chinese Communist Party, has not been studied much by scholars inside or outside of China. Originally an authoritative translation house for classical Marxist works, in recent years CCTB has gained more prominence as a think tank. Among its leaders are well-known advocates for political reforms and democracy. This article presents an analytical history of CCTB. It will discuss how did CCTB evolve, what factors played the major role in its evolution, and how does it reconcile its seemingly contradictory roles of being a Marxist translation house and a pro-reform think tank.